Semiconductor light emitting device for display pixel and display apparatus including same

Through magnetic assisted dielectrophoretic self-assembly technology (MDSAT), combining magnetic and dielectrophoretic forces, efficient synchronous self-assembly of micro LEDs is achieved, solving the obstacles to transfer and assembly of micro LEDs in the large-scale market, and achieving high yield and production scalability.

CN119604976APending Publication Date: 2025-03-11LG ELECTRONICS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380055276.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-19
Filing Date
2023-07-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Micro LED displays have barriers to high processing volume, high yield and production scalability, especially in high volume markets that are difficult to achieve efficient transfer and assembly.

Method used

Magnetic assisted dielerophoretic self-assembly technology (MDSAT) is used to combine magnetic and dielerophoretic forces to achieve synchronous self-assembly of RGB LEDs, improve transfer yield, and accurately control the assembly direction of LED chips.

Benefits of technology

Achieving a simultaneous transfer yield of 99.99% RGB LEDs in 15 minutes ensures efficient assembly and production scalability of micro LEDs, and is suitable for commercial product production in large-scale markets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604976A_ABST
    Figure CN119604976A_ABST
Patent Text Reader

Abstract

The invention relates to a semiconductor light emitting device for display pixels and a display apparatus including the same. The semiconductor light emitting device for display pixels according to the present invention may include: a light emitting structure including a first conductivity type semiconductor layer, an active layer, and a second conductivity type semiconductor layer; a first contact electrode electrically connected to the first conductive type semiconductor layer; a metal layer disposed below the first conductive type semiconductor layer; a second contact electrode disposed on the second conductive type semiconductor layer; and a passivation layer disposed on the light emitting structure. The metal layer may include a magnetic substance, and a ratio of a weight of the magnetic substance to a weight of the semiconductor light emitting device may be 0.25% to 36.75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present embodiment relates to a semiconductor light emitting device for a display pixel and a display apparatus including the same.

[0002] Specifically, the present embodiment relates to a synchronous self-assembly technology of RGB Micro-LEDs for next-generation displays, a semiconductor light-emitting device for display pixels applicable to the technology, and a display device including the same. Background Art

[0003] Compared with organic light-emitting diode (OLED) displays, micro-LED displays have many advantages such as long life and high brightness, and therefore have attracted much attention as next-generation displays. As a result, micro-LED technology is being used for commercialization of large-screen displays such as digital signage, and is also being actively researched and developed for other application fields such as augmented reality, flexible displays, and in vivo imaging.

[0004] However, from the perspective of micro-LED transfer technology, high throughput, high yield, and production scalability to more than 10 generations (2940×3370mm 2 ) There are major hurdles in terms of glass size that must be overcome if micro-LEDs are to enter the mainstream product market and compete with LCD and OLED.

[0005] Although there have been some developments in transfer technologies such as stamping and fluid self-assembly (FSA) in the related technologies, such related technologies are only applicable to the small-volume market and there is no practical solution for the large-volume market.

[0006] For example, the related art stamp method has demonstrated the transfer of red, blue and green light emitting diodes (RGB) LEDs into individual RGB sub-pixels. However, limitations such as poor repeatability and limited stamp size prevent high transfer throughput.

[0007] In addition, configuration accuracy is another issue. The spacing between the anode and cathode of the micro-LED used for electrical connection and the area of ​​the electrical pad are designed considering the configuration accuracy. If the configuration accuracy is poor, the size of the micro-LED will be limited.

[0008] In contrast, the related art FSA (Fluidic Self-Assembly) uses fluid to transfer micro-sized devices, the micro-sized devices are attached to molten solder, and are self-aligned in assembly holes by minimizing the surface free energy of the liquid solder.

[0009] However, the best method for moving the LED to the assembly hole has not yet been determined.

[0010] For example, although tumbling motion, gravity, swinging motion, etc. have been proposed for transferring ultra-small devices, they all have the common disadvantage that the transfer yield is not sufficient for commercialization.

[0011] Furthermore, unresolved barriers to the commercialization of FSA remain the biggest issue.

[0012] First, in order to meet the needs of high-volume consumer markets such as TVs, high-throughput transfer is required. In order to make micro-LED products cost-compatible with most consumer application products, a transfer speed of 50 million to 100 million LEDs per hour has been proposed as a target level.

[0013] The fastest FSA process reported to date is 62,500 chips every 45 seconds, which is equivalent to about five million chips per hour. Based on this speed, it would take up to five hours to assemble a single 4K resolution micro-LED display consisting of 25 million LEDs.

[0014] Second, scalable technologies are needed for transferring micro-LEDs to production-scale substrates.

[0015] Third, a technical solution is needed to ensure selective FSA for RGB micro-LEDs. To date, most research on micro-LED FSA has been performed using only single-color LEDs. Shape-matched FSA technology has been proposed as a potential solution for RGB LED assembly, but its feasibility has only been demonstrated using silicon components larger than 100μm.

[0016] On the other hand, in the technology using fluid assembly, it is very important to distinguish the chip assembly direction in order to correctly connect the n-type contact area and the p-type contact area in the LED chip with the lighting wiring.

[0017] However, in the related art, there is no technology that can achieve more than 90% of the assembly directions of micro LEDs. Summary of the invention

[0018] Problem that the invention aims to solve

[0019] One of the technical issues of the present invention is to overcome the barriers of transfer technology in micro-LED technology.

[0020] For example, the present invention is to overcome the problems such as high throughput, high yield, production scalability to more than 10 generations (2940×3370mm 2 )The main obstacle in glass size.

[0021] In addition, one of the technical problems of the present invention is to accurately control the assembly direction of LED chips using fluid assembly technology.

[0022] The technical problems of the present invention are not limited to the problems described in this section, and include the contents that can be understood from the description of the invention.

[0023] Technical solutions to the problem

[0024] The semiconductor light-emitting device for display pixels of the embodiment may include: a light-emitting structure including a first conductive semiconductor layer, an active layer and a second conductive semiconductor layer; a first contact electrode electrically connected to the first conductive semiconductor layer; a metal layer arranged under the first conductive semiconductor layer; a second contact electrode arranged on the second conductive semiconductor layer; and a passivation layer arranged on the light-emitting structure.

[0025] The metal layer may include a magnetic substance, and a ratio of a weight of the magnetic substance to a weight of the semiconductor light emitting device may be 0.25% to 36.75%.

[0026] The magnetic substance may include Ni.

[0027] The thickness of the magnetic substance may be 10 nm to 2300 nm.

[0028] The first contact electrode may be configured to surround the second contact electrode, and the first contact electrode may be electrically connected to the first conductive semiconductor layer from which a portion of the upper side of the light emitting structure is removed.

[0029] In addition, the display device of the embodiment may include: a first assembly electrode and a second assembly electrode separated from each other; a dielectric layer, arranged on the first assembly electrode and the second assembly electrode; an insulating layer, having a specified assembly hole, arranged on the dielectric layer; and a semiconductor light emitting device, arranged in the assembly hole.

[0030] The semiconductor light emitting device may include any of the semiconductor light emitting devices.

[0031] The height of the assembly hole may be greater than 4.0 μm.

[0032] The height of the assembly hole may be 4.5 μm to 5.0 μm.

[0033] The dielectric layer may include nitride.

[0034] The dielectric layer may include Si3N4.

[0035] A gap ratio, which is a ratio of a distance between the first and second assembly electrodes spaced apart to a size of the semiconductor light emitting device, may be 0.4 to 0.8.

[0036] Effects of the Invention

[0037] The present invention can propose a new transfer method named MDSAT (Magnetic force-assisted Dielectrophoretic Self-Assembly Technology) based on FSA (Fluidic Self-Assembly) technology.

[0038] The MDSAT technology of the present invention has a special technical effect, that is, by combining magnetic force and dielectrophoresis (DEP) force, a 99.99% RGB LED synchronous transfer yield can be achieved within 15 minutes.

[0039] Furthermore, according to the present invention, nickel, which is a ferromagnetic material, is precisely inserted into the micro-LED, thereby achieving a special technical effect of not only being able to move the micro-LED using a magnet but also being able to precisely control the vertical assembly direction.

[0040] For example, according to the embodiment, the micro-LED can be effectively moved by magnetic force in the fluid, and the DEP force (DEP force, dielectrophoresis force) can be used to assemble the disc-shaped LED chip with the back metal. This has a special technical effect, that is, by perfectly controlling the assembly direction, it is possible to ensure a 99.99% assembly rate (or transfer rate) that can be mass-produced as a display device.

[0041] In addition, according to the present invention, by applying a local DEP force centered on the assembly hole, there is a technical effect that such a micro LED can be effectively captured in the assembly hole and assembled. The assembly hole can be called a receiving body.

[0042] In addition, according to the present invention, there is a technical effect that RGB LEDs can be assembled synchronously through shape matching between micro LEDs and assembly holes.

[0043] Furthermore, according to the embodiment, a light emitting panel was fabricated and exhibited damage-free transfer characteristics and uniform RGB electroluminescent emission, which demonstrates that the MDSAT method of the embodiment is an excellent transfer technology candidate for mass production of mainstream commercial products.

[0044] According to the embodiment, an MDSAT method is proposed for high-speed and synchronous transfer of RGB LEDs to a large-area substrate using a combination of magnetic force and dielectrophoresis (DEP). Under the action of magnetic force and DEP force, the RGB LEDs are captured into the assembly holes and self-aligned, so the transfer yield is excellent compared with the FSA method of the related technology.

[0045] Furthermore, the MDSAT of the embodiments is a scalable process that can cover the size of glass in today's display production. For example, the time it takes for the magnet array to cover the glass can remain constant by simply scaling up the size of the magnet array to match the glass. Therefore, the assembly time is not affected by the transfer area and the number of assembly holes in the glass. This is in stark contrast to the die transfer method where the process time increases linearly with the transfer area.

[0046] The present invention achieves a 99.99% RGBLED transfer yield by optimizing assembly conditions, assembly hole design, and shape matching, which is more suitable for achieving a defect-free 4K resolution display when used with RPA (Redundancy Pixel Architecture). Therefore, the MDSAT of the embodiment is considered to be an ideal micro-LED transfer technology for mass production of next-generation commercial products.

[0047] The technical effects of the present invention are not limited to the contents described in the content of the present invention, but also include the contents grasped from the description of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1a It is a diagram schematically showing the MDSAT (Magnetic force-assisted Dielectrophoretic Self-Assembly Technology) method of the embodiment.

[0049] Figure 1b are the data of DEP and magnetic force distribution between two adjacent assembly holes (AH).

[0050] Figure 2 is an illustrative diagram of the relationship between the DEP force and the tilt angle of the micro-LED at the surface of the assembly hole (AH) and the assembly substrate (AS) surface in the embodiment.

[0051] Figure 3 is an illustrative diagram of a micro LED device according to an embodiment.

[0052] Figure 4 These are the simulation results of the DEP force vector for various micro-LED assembly angles (0-180°) relative to the assembly hole surface.

[0053] Figures 5 to 7 is the behavior of a single-color micro-LED near the assembly hole (AH).

[0054] Figure 8a It is the transfer yield data associated with DEP force and magnetic force.

[0055] Figure 8b This is transfer yield data related to the thickness of the back metal and the magnetic force.

[0056] Figure 8c It is a comparison data of the forward DEP force and the reverse DEP force based on whether the LED chip has a bottom metal layer.

[0057] Fig. 9 a to Fig. 9 c is a diagram showing the assembly state of the micro LED according to the relationship between the magnetic force and the DEP force.

[0058] Fig.10 This is experimental result data used to evaluate the reproducibility of transfer yield.

[0059] Fig.11 are images of three instances of shape mismatch defects.

[0060] Fig.12 is a schematic diagram showing the tilt angle between the shape-mismatched micro-LED and the assembly hole.

[0061] Fig.13 is a graph of DEP force data for shape-mismatched micro-LEDs as a function of assembly hole height.

[0062] Fig.14 : is the data of transfer yield as a function of assembly hole height in the examples.

[0063] Fig.15a is a schematic diagram of a PM panel showing red, green, and blue LEDs and the connections between the LEDs and pads.

[0064] Fig.15b It is a cross-sectional view of the RGB panel.

[0065] Fig.15c It is a graph showing IV characteristics of red, green, and blue.

[0066] Fig.15d The EL spectrum data show emission peaks at 451 nm, 532 nm, and 630 nm, respectively.

[0067] Fig.17 It is the data of the change of DEP force according to the frequency.

[0068] Fig.18 Data showing the variation of DEP force as a function of frequency when using RGB micro-LEDs with a bottom metal layer.

[0069] Fig.19 This is a schematic diagram of the 3D model used for COMSOL simulation. DETAILED DESCRIPTION

[0070] Hereinafter, the embodiments disclosed in this specification will be described in detail with reference to the accompanying drawings. The suffixes "module" and "unit" of the constituent elements used in the following description are given or used interchangeably for the convenience of writing the specification, and they themselves do not have mutually distinguishing meanings or functions. In addition, the accompanying drawings are used to easily understand the embodiments disclosed in this specification, and the technical ideas disclosed in this specification are not limited to the accompanying drawings. In addition, when it is mentioned that an element such as a layer, a region or a substrate exists "on" another constituent element, it includes that it may exist directly on another constituent element, or other constituent elements may exist in the middle.

[0071] The display device described in this specification may include a digital TV, a portable mobile phone, a smart phone, a laptop computer, a digital broadcast terminal, a PDA (personal digital assistant), a PMP (portable multimedia player), a navigation, a tablet computer (Slate PC), a tablet PC, an ultrabook, a desktop computer, etc. However, even if the configuration of the embodiment described in this specification is a new product form to be developed in the future, it can also be applied to a device capable of displaying.

[0072] Hereinafter, a light-emitting device for a display pixel and a display device including the same according to an embodiment will be described.

[0073] Figure 1a This is a diagram schematically showing the MDSAT (Magnetic force-assisted Dielectrophoretic Self-Assembly Technology) method of the embodiment.

[0074] according to Figure 1a , showing a micro LED (MLD) and an assembled substrate (AS) placed in a water tank chamber with deionized water used as a fluid medium (FM; fluidic medium).

[0075] According to an embodiment, as shown in the accompanying drawings, an assembly substrate (AS) and micro-LEDs are arranged in a water tank chamber, and a micro-LED cluster can be formed under the axial rotation of a magnet located below the assembly substrate. The magnet can maintain the axial rotation and move in the direction of the arrow.

[0076] In addition, according to an embodiment, in order to apply magnetic force to a strong magnetic material, such as a micro-LED (MLD) built with nickel, a magnetic array (MA) may be arranged along the back side of the assembly substrate (AS). The magnetic array (MA) may include a plurality of circular magnetic bar arrays, but the embodiment is not limited thereto. A method for manufacturing micro-LEDs will be described later.

[0077] Figure 1a , the micro-LED (MLD) is shown to be arranged on the upper side of the assembly substrate (AS), but the embodiment is not limited thereto. For example, the micro-LED (MLD) may also be arranged on the lower side of the assembly substrate (AS).

[0078] Reference Figure 1a First, an axial rotational motion is provided to the magnetic bars of each magnet array (MA) so that a large number of micro LEDs (MLD) are gathered around it. Then, the magnet array (MA) can be moved along the X-axis and Y-axis directions to scan the entire area of ​​the assembly substrate (AS).

[0079] like Figure 1a As shown, the micro-LED cluster moves in response to the magnetic force of the magnet array (MA), and as it approaches the assembly hole (AH), the individual micro-LEDs in the cluster are captured in each assembly hole (AH) under the action of the DEP force.

[0080] Then, Figure 1b The DEP and magnetic force distribution between two adjacent assembly holes (AH) are shown.

[0081] The necessary magnetic force and DEP are shown as dashed and solid lines, respectively, and a line diagram in the background of the diagram shows the positions where the magnetic force and DEP are calculated.

[0082] In an embodiment, the DEP force may exceed the magnetic force by about 10 times, which may control the final assembly process.

[0083] On the other hand, since the DEP of the embodiment is a short-range force, it can be controlled to work effectively around the assembly hole (AH). In contrast, the magnetic force can work over a longer distance, helping to move the micro-LED across the assembly substrate (AS).

[0084] Figure 2 is an illustrative diagram of the relationship between the DEP force and the tilt angle of the micro-LED at the surface of the assembly hole (AH) and the surface of the assembly substrate (AS) in an embodiment.

[0085] According to an embodiment, various movements of a micro-LED caused by a DEP force generated by an assembly electrode (AE) when the micro-LED approaches an assembly hole (AH) at various angles relative to a surface of an assembly substrate (AS) have been studied.

[0086] Reference Figure 2 , in the angle range of In the cross-sectional view of the 3D model (upper left), the metal layer (B-metal) on the back of the micro-LED moves toward the assembly electrode (AE).

[0087] On the contrary, In the cross-sectional view of the 3D model with an angle range (upper right), as the angle of the curve increases within 90 to 180°, the passivation layer (PV) at the top of the micro-LED moves along the direction of the assembly electrode (AE).

[0088] Figure 3 is an illustrative diagram of a micro LED device according to an embodiment.

[0089] For example, Figure 3 (a) is an illustration of a blue or green micro LED device of the first embodiment.

[0090] The blue or green micro LED device of the first embodiment may include undoped GaN (u-GaN), n-type GaN (n-GaN), an active layer (not shown), and p-type GaN (p-GaN).

[0091] For example, the blue or green micro LED device of the first embodiment may include a bottom metal (B-metal) under undoped GaN (u-GaN), an n-type contact electrode (n-contact) on n-type GaN (n-GaN), a p-type contact electrode (p-contact) on p-type GaN (p-GaN), and a passivation layer (PV). The n-type contact electrode (n-contact) and the passivation layer (PV) may be separated by a specified distance S.

[0092] The blue or green micro LED device of the first embodiment may be a GaN-based disk, and the bottom metal (B-metal) may include Ti (titanium), but is not limited thereto.

[0093] In addition, the p-type contact electrode (p-contact) may be formed of ITO (Indium Tin Oxide), but is not limited thereto.

[0094] In addition, the n-type contact electrode (n-contact) may be formed of a single layer or a composite layer of Cr (chromium), Ti, or Ni.

[0095] In addition, in the first embodiment, the thickness of the undoped GaN (u-GaN) may be about 3.0 to 4.0 μm. In addition, the thickness of the n-type GaN (n-GaN) may be about 3.0 to 4.0 μm. In addition, the thickness of the p-type GaN (p-GaN) may be about 0.2 to 1.0 μm.

[0096] The bottom metal (B-metal) may have a thickness of about 50 to 200 nm. The passivation layer (PV) may include SiO2, and the thickness thereof may be about 300 to 800 nm.

[0097] Then, Figure 3 (b) is an illustrative diagram of a red micro LED device of the second embodiment.

[0098] The red micro LED device of the second embodiment may include n-type GaInP (n-GaInP; n-type gallium indium phosphide), n-type GaAs (n-GaAs; n-type gallium arsenide), n-type AlInP (n-AlInP; n-type aluminum indium phosphide), an active layer (not shown), and p-type GaP (p-GaP; p-type gallium phosphide).

[0099] For example, the red micro LED device of the second embodiment may include a bottom metal (B-metal) under n-type GaInP (n-GaInP), an n-type contact electrode (n-contact) on n-type AlInP (n-AlInP), a p-type contact electrode (p-contact) on p-type GaP (p-GaP) and a passivation layer (PV). The n-type contact electrode (n-contact) and the passivation layer (PV) may be separated by a specified distance S.

[0100] The red micro LED device of the second embodiment may be a GaAs-based disk, and the bottom metal (B-metal) may include Ti, but is not limited thereto.

[0101] In addition, the n-type contact electrode (n-contact) may be formed of a single layer or a composite layer of Au (gold), AuGe (gold-germanium alloy), Ti, or Ni.

[0102] In addition, the p-type contact electrode (p-contact) may be formed of ITO, but is not limited thereto.

[0103] Furthermore, in the second embodiment, the thickness of n-type GaInP (n-GaInP) may be approximately 0.1 to 0.5 μm.

[0104] In addition, the thickness of n-type GaAs (n-GaAs) may be about 0.02 to 0.10 μm. In addition, the thickness of n-type AlInP (n-AlInP) may be about 3.0 to 5.0 μm. In addition, the thickness of p-type GaP (p-GaP) may be about 0.5 to 1.5 μm.

[0105] The bottom metal (B-metal) may have a thickness of about 50-200 nm. The passivation (PV) may include SiO2, and the thickness thereof may be about 300-800 nm.

[0106] Figure 4 These are the simulation results of the DEP force vector for various micro-LED assembly angles (0-180°) relative to the assembly hole surface.

[0107] According to an embodiment, COMSOL simulation using a finite element method studies the relationship of the DEP force between the micro-LED and the assembly hole (AH) by integrating the Maxwell stress tensor over the surface.

[0108] When the induced dipole of a particle interacts with an inhomogeneous electric field, the DEP force acts on the particle to move it, and the information about the direction of movement of the particle is provided by the sign of the Clausius-Mossotti (CM) coefficient. For example, if the coefficient is positive or negative, the particle is attracted to or repelled from the maximum of the electric field strength accordingly.

[0109] Refer again Figure 2 , Figure 2 The Z-axis components of the DEP force vector in the assembly electrode (AE) direction are shown, with cross-sectional views inserted for the positions of the micro-LEDs for angles of 0-90° and 90-180°.

[0110] according to Figure 2 , showing that the DEP force increases as the angle decreases. This shows that as the angle decreases, the micro-LED is pulled toward the assembly hole, and finally assembly is achieved when the angle is less than 10°, when the DEP force dominates the magnetic force.

[0111] In the proposed MDSAT method, the axial rotation of the magnets that guide the swinging motion of the micro-LED is expected to increase the probability that the micro-LED will meet this angular reference for assembly.

[0112] However, if the angle exceeds 60°, the DEP force fluctuates around 0 and becomes significantly negative after 165°. This indicates that the micro-LED may be pushed away from the assembly hole (AH) at angles above 60°, especially in the presence of external magnetic forces.

[0113] This unique action is attributed to the design of the micro-LED, whose bottom side exhibits higher conductivity due to an intentionally applied bottom metal layer (B-metal).

[0114] To experimentally verify the simulation results, an ultra-high-speed camera was used to monitor the behavior of a monochromatic micro-LED (GaN-based disk with a diameter of 38 μm) near the assembly hole (AH). The recorded videos show the appearance of stages 1 to 3 at Figure 5 (Phase 1 above), Figure 6 (Phase 2 above) and Figure 7 (Stage 3 above) is shown.

[0115] first, Figure 5 (a) and Figure 5 (b) shows stage 1 where the micro-LEDs gather around the assembly hole (AH) in response to the movement of the magnetic force. The micro-LEDs closest to the assembly hole (AH) respond to the generated DEP force and their edges meet the periphery of the assembly hole.

[0116] Then, Figure 6 (a) and Figure 6 (b) shows the second stage where the micro-LED swings along the edge of the assembly hole (AH) in response to the rotational motion of the magnet. This represents a transition state where a balance is formed between the DEP and the magnetic force.

[0117] at last, Figure 7 (a) and Figure 7 (b) shows that as the angle between the micro-LED and the assembly hole (AH) decreases below a certain angle, the micro-LED is assembled.

[0118] According to an embodiment, based on the described behavior of the micro-LEDs in the assembly hole (AH), the transfer yield with the variation of the applied peak-to-peak voltage (Vpp) associated with DEP was studied.

[0119] Then, Figure 8a The transfer yield obtained experimentally is presented together with the DEP force and magnetic force calculated in COMSOL simulation. The magnetic force was calculated at 10 locations around the assembly hole (AH). The results range from 1×10 -8 [N]~1.2×10 -7[N] The size of the assembly substrate is about 75 mm x 75 mm, about 270 x 240 pixels. The assembly substrate is composed of about 64,800 assembly holes (AH), which are spaced 278 μm apart from each other.

[0120] like Figure 8a As shown in FIG. 1 , as Vpp increases to a maximum value, the transfer yield increases initially and then begins to decrease. This phenomenon deviates from the intuitive prediction that the yield will increase with the increase of the DEP force controlled by Vpp.

[0121] To illustrate this behavior, a CCD camera was used to capture images of the assembly site and image analysis was performed. The image analysis results revealed defects such as multiple micro-LEDs in one housing and unassembled areas, which reduced the transfer yield.

[0122] Then, Figure 8b This is transfer yield data related to the thickness of the back metal and the magnetic force.

[0123] Reference Figure 8a and Figure 8b , using magnetic force to effectively move micro-LEDs in the fluid, and using DEP force to assemble disc-shaped LED chips with metal on the back to accurately control the assembly direction, thus having a special technical effect that can ensure an assembly rate or transfer rate of 99.99%.

[0124] Then, Figure 8c It is the comparison data of the forward and reverse DEP forces based on whether the LED chip has a bottom metal layer.

[0125] Reference Figure 8c In the LED chip (LED_E) of the embodiment, a bottom metal may be provided at the bottom of the chip. In contrast, in the LED (LED_R) according to the comparative example, no bottom metal may be provided at the bottom of the chip.

[0126] If reverse power is applied to the LED chip of the embodiment (LED_E) and the LED of the comparative example (LED_R), repulsive force may be applied to the chip, and thus the LED chip may be away from the assembly hole.

[0127] On the contrary, if forward power is applied to the LED chip of the embodiment (LED_E) and the LED of the comparative example (LED_R), an attractive force can be applied to the chip, thereby allowing the LED chip to be assembled in the assembly hole.

[0128] Since the semiconductor light emitting device of the embodiment has a back metal layer, it is more conducive to distinguishing the upper and lower parts of the chip, thereby being able to perfectly control the assembly direction.

[0129] For example, according to the embodiment, there is a technical effect that the DEP force during forward assembly is significantly increased by more than 50% compared to the DEP force during reverse assembly.

[0130] For example, refer to Figure 8c The LED chip (LED_E) of the embodiment may have a back metal, and the difference (ΔDEP_E) between the DEP force when the reverse power is applied and the DEP force when the forward power of 7V is applied may be about 3.0X10 -6 [N].

[0131] In contrast, in the LED chip (LED_R) of the comparative example, the difference (ΔDEP_R) between the DEP force when the reverse power is applied and the DEP force when the forward power of 7V is applied can be about 2.0×10 -6 [N].

[0132] Therefore, the semiconductor light-emitting device of the embodiment has a back metal layer, which is more conducive to distinguishing the upper and lower parts of the chip, thereby having a special technical effect of being able to perfectly control the assembly direction.

[0133] Next, Table 1 below shows the data of the thickness, weight, and ratio of Ni according to the strength of the magnet in the Examples.

[0134] The semiconductor light emitting device of the embodiment may include a back metal layer, and the back metal layer may include a magnetic substance. For example, the back metal layer of the embodiment may include Ni, but is not limited thereto.

[0135]

Table 1

[0136]

[0137] Table 1 is based on the strength of the magnet, in order to have about 1.2E-7 [N] (refer to Figure 1b )'s magnetic Ni thickness and the corresponding Ni ratio change data.

[0138] For example, the magnetic force for 38 μm-level DSAT assembly in the embodiment may be about 1.2E-7 [N]. According to the embodiment, the ratio of Ni in the semiconductor light-emitting device chip may be about 0.25% to 36.75%.

[0139] The experimental conditions in the embodiment can use 12Vpp, frequency 100kHz, 430mT neodymium magnet with a size of 2mm×20mm, and the distance between the micro LED and the magnet can be about 504.78μm. The thickness of the glass can be about 500μm, and the thickness of the electrode and the passivation layer can be about 0.28μm. The height of the assembly hole can be about 4.5μm, the magnet (Ni) thickness of the GaN-based LED can be 220nm, and the electrode gap can be about 7.5μm, but it is not limited to this.

[0140] According to an embodiment, the DEP force may be greater than the magnetic force by more than about 10 times, for example, by about 12 times. For example, according to an embodiment, the DEP force may be about 1.47E-6 [N] ( Figure 1b ), the magnetic force can be about 1.2E-7[N], but is not limited to this.

[0141] Fig. 9 a to Fig. 9 c is a diagram showing the assembly state of the micro LED according to the relationship between the magnetic force and the DEP force.

[0142] also, Fig.10 This is experimental result data used to evaluate the reproducibility of transfer yield.

[0143] Fig. 9 (a) shows the initial stage when the magnetic force dominates the DEP force. For example, it shows that the micro LED placed at the assembly hole position is swept away by the movement of the magnet, resulting in Fig. 9 (a) Shown in the unassembled position.

[0144] Then, if Fig. 9 As shown in (b), as Vpp and DEP force increase to a level above the magnetic force, the empty assembly hole (AH) is gradually filled with micro-LEDs (MLD) and remains stable.

[0145] Then, if Fig. 9 As shown in (c), after reaching 12Vpp, the transfer yield begins to decrease. Fig. 9 As shown in (c), it is caused by the defect that multiple micro-LEDs (MLD1, MLD2) are arranged around an assembly hole (AH).

[0146] Due to design tolerance, after the micro-LED is assembled in the assembly hole (AH), a gap may be generated between the micro-LED and the wall of the assembly hole (AH).

[0147] A certain level of DEP force is inherently generated through the gap, and if the DEP force becomes strong enough at higher Vpp, it can capture other nearby micro-LEDs.

[0148] In order to evaluate the reproducibility of the transfer yield, the experiment was repeated 15 times at the optimal voltage (12 Vpp). Fig.10 shown.

[0149] According to the embodiment, the synchronous self-assembly of RGB micro-LEDs was performed, and it was verified that a high assembly yield can be obtained using the proposed MDSAT method.

[0150] The shape of the assembly hole (AH) matches the shape of the respective RGB micro-LED, and the size of the assembly hole (AH) is designed to be 4μm larger than the LED in both axis directions.

[0151] For example, the diameter of the red micro-LED (R-MLD) is 42μm, the diameter of the green micro-LED (G-MLD) is 49μm×35μm, and the diameter of the blue micro-LED (B-MLD) is 56μm×28μm.

[0152] Based on this design, the assembly yield of the micro LED fixed in the assembly hole is 99.81%.

[0153] There are a total of 6 combinations of shape mismatch defects. For example, the red micro-LED (R-MLD) may be located in the green assembly hole or the blue assembly hole, the green micro-LED (G-MLD) may be located in the red assembly hole or the blue assembly hole, and the blue micro-LED (B-MLD) may be located in the red assembly hole or the green assembly hole.

[0154] Fig.11 are images of three instances of shape mismatch defects.

[0155] Reference Fig.11 , showing a red micro-LED (R-MLD) placed in a green assembly hole (G-AH), a green micro-LED (G-MLD) placed in a red assembly hole (R-AH), a blue micro-LED (B-MLD) placed in a green assembly hole (G-AH), and an anode and a cathode.

[0156] Fig.12 is a schematic diagram showing the tilt angle between the shape-mismatched micro-LED and the assembly hole.

[0157] A closer look at the defects revealed that the micro-LEDs were assembled in a tilted manner.

[0158] like Fig.12 As shown, one side of the micro LED (MLD) is located at the lower corner of the assembly hole, and the other diagonal side is located above the assembly hole.

[0159] like Fig.12 As shown, θi can be defined as the tilt angle between the micro-LED and the assembly hole.

[0160] Fig.13 Figure 3 is a graph of the DEP force for morphologically mismatched micro-LEDs as a function of assembly hole height.

[0161] In order to carefully investigate such shape mismatch defects, Fig.13 As shown, the DEP forces at various θ are quantitatively analyzed as a function of assembled pore height for all six combinations of shape mismatch.

[0162] The maximum value of the magnetic force acting on the micro LED is 1.2×10 -7 [N], as shown on the diagram.

[0163] As the height of the assembly hole (AH) increases from 3 μm to 5 μm, θ increases, and as a result, the DEP force applied to the micro LED decreases.

[0164] If the height of the assembly hole (AH) increases above about 4.3 μm, the DEP level drops below the magnetic level for all six morphology mismatch examples.

[0165] This means that if the assembly hole (AH) height is 4.3 μm or more, there is a high possibility that the defective assembled micro-LED will be separated as the magnet moves.

[0166] This process is continued until a micro-LED with a suitable shape is obtained, at which point θ is close to 0 and the micro-LED is difficult to separate.

[0167] This finding provides important insights, indicating that increasing the height of the assembly hole (AH) can enhance the self-repair of pattern mismatch defects.

[0168] Fig.14 : is the data of transfer yield as a function of assembly hole height in the examples.

[0169] According to the embodiment, based on the above understanding, the transfer yield of the function of the assembly hole height ranging from 3 μm to 5 μm is studied, and Fig.14 The results are shown.

[0170] The size of the assembly substrate is 75mm×75mm, and it consists of 64,800 RGB assembly holes separated by 278μm from each other.

[0171] The magnet head, which is the same size as the assembly substrate, consists of an 8×8 magnet array, and each magnet is designed to scan a 13mm×13mm area synchronously within 15 minutes.

[0172] The magnetic field strength of each neodymium magnet bar (diameter: 5 mm, length: 20 mm) is 5000 Gauss. The magnetic array can rotate 420 revolutions per minute along the axis while moving at 250 μm / s in the x and y directions.

[0173] like Fig.14 As shown, the transfer yield is greatly improved as the assembly hole height increases as a result of the reduction of shape mismatch defects.

[0174] By increasing the assembly hole height from 3μm to 4μm, the transfer yield and defect rate are greatly improved. If the assembly hole height reaches 4.5μm and 5μm, the transfer yield reaches 99.99%.

[0175] To the best of the inventors' knowledge, this is the first study demonstrating the simultaneous delivery of RGB micro-LEDs with the highest transfer yield for FSA technology, independent of the type and size of the assembled devices.

[0176] Furthermore, according to the embodiment, a 100 mm×100 mm RGB micro LED display panel is manufactured using the MDSAT method. In previous studies, although micro LED displays based on FSA were reported, they were based on monochrome LEDs.

[0177] In contrast, the panel of the embodiment is composed of 43,200 micro LEDs with a display resolution of 120×120 pixels and a pixel pitch of 834 μm.

[0178] Fig.15a is a schematic diagram of a PM panel showing red, green, and blue LEDs and the connections between the LEDs and pads.

[0179] Fig.15b is a cross-sectional view of an RGB panel. For example, Fig.15b A focused ion beam (FIB) image of a cross-sectional view of a PM panel is shown, demonstrating two coplanar assembly electrodes, micro-LEDs within assembly holes, a planarization layer, and electric field lines.

[0180] Since the similar contrast between organic substances leads to blurred representation of the assembly pore, the assembly pore is represented by a white dotted line.

[0181] According to the embodiment, after self-assembly, a spraying process is performed to fix the micro LEDs, and then planarization is performed and contact holes are made to connect power lines for anode and common electrodes and pads.

[0182] Fig.15b A cross-sectional view of an RGB panel showing these components is shown.

[0183] Then, Fig.15cIt is a graph showing IV characteristics of red, green, and blue.

[0184] For example, Fig.15c The IV characteristics of the red micro LED with a forward voltage of 1.83V, the IV characteristics of the green micro LED with a forward voltage of 2.3V, and the IV characteristics of the blue micro LED with a forward voltage of 2.65V at a leakage current of 10μA and less than 10nA are shown.

[0185] Then, Fig.15d EL spectra showing emission peaks at 451 nm, 532 nm, and 630 nm are provided, respectively.

[0186] According to the embodiment, electroluminescence (EL) emission of the RGB panel with excellent luminous intensity and brightness uniformity is shown, and 3×3 pixels emitting clear red, green, and blue light can be realized.

[0187] In terms of pixel yield, the corresponding panel has 10 defective pixels, showing a 99.98% luminous pixel yield.

[0188] The scalable MDSAT approach can also scale the magnet array size accordingly, potentially integrating with existing active-matrix (AM) backplanes.

[0189] In the case of large-area glass, it is necessary to consider the RC delay caused by the increase in wiring of the assembly electrode. However, this delay can be overcome by using a circuit structure with multiple pads to apply AC voltage in block units. If the MDSAT method is integrated with the existing AM backplane, RGB micro-LEDs can be deposited on a transistor backplane with a front release structure. Then, the anode of the micro-LED can be connected to the drive circuit of the AM backplane, and the cathode is connected together.

[0190] Experimental Example 1

[0191] RGB LEDs: Difference in DEP force between AlGaInP-based and GaN-based LEDs.

[0192] In recent years, there has been an increasing amount of research into the self-assembly of micro-components such as LEDs, III-V devices, and nanowires using DEP forces.

[0193] In this experiment, the DEP forces on various RGB micro-LEDs were compared. A 3D model of the micro-LEDs was constructed using COMSOL and used to calculate the DEP forces on an AlGaInP-based LED for the red case and a GaN-based LED for the blue and green cases.

[0194] Table 2 below shows the materials, permittivity, and conductivity as input medium variables for COMSOL. The thin layers of multi-quantum wells (MQWs) were not included in the COMSOL simulations because they were expected to have minimal impact on the results.

[0195]

Table 2

[0196]

[0197] The DSAT of the embodiments has yet another important potential, namely the ability to simultaneously assemble RGB micro-LEDs by matching the RGB LEDs to the respective assembly hole shapes.

[0198] If the pattern of micro-LED and assembly hole is differentiated, RGBLED can be transferred at one time in one chamber, so the system design is simple and the investment cost is reduced, and it has the advantages of minimizing engineering cost, etc.

[0199] In this work, a circular shape was selected for the red micro-LED, and two elliptical shapes with different major and minor axis lengths were used for the green and blue micro-LEDs.

[0200] The reason for selecting a circle and two ellipses is as follows: In the MDSAT method, self-assembly is performed in a random manner, so a large number of micro-LEDs are randomly distributed in a turbulent flow generated by the magnetic force of a rotating magnet.

[0201] Therefore, the arbitrary movement of a large number of micro-LEDs overcomes the rotational symmetry dependence of the self-assembly, so there is no gap in assembly yield between circular and elliptical shapes.

[0202] In addition, compared with shapes with edges and corners (such as triangles, regular quadrilaterals, or rectangles), circles and ellipses are more resistant to damage caused by LED-to-LED collisions due to their rounded shapes.

[0203] For the size of the circular red micro-LED, two factors were considered: the design rule (the allowable error for making one anode (p-type contact) and two cathodes (n-type contacts) on a single micro-LED) and the separation S between the Ni metal and the edge of the micro-LED.

[0204] In the experimental example, the design rule is set to 7 μm, which means that 35 μm is required for three regions of three contacts and two spaces between the contacts.

[0205] like Figure 3 (a) and Figure 3As described in (b), the purpose of separation is to remove the LED-LED chain connection formed by magnetization after self-assembly.

[0206] Fig.16 is a microscope image of the RGB micro LED of the embodiment.

[0207] For example, Fig.16 (a) is an image of a red LED based on AlGaInP with a micro-LED size of 38 μm in diameter. Fig.16 (b) is an image of a GaN-based green LED with a micro-LED size of 45μm×31μm. In addition, Fig.16 (c) is an image of a GaN-based blue LED with a micro-LED size of 52 μm × 24 μm (scale bar is 20 μm).

[0208] Reference Fig.16 (a), the separation S is set to 1.5 μm on both sides (left and right) of the micro-LED. Therefore, considering the design rule (35 μm) and the two separations (3 μm), the diameter of the red micro-LED (R-MLD) is set to 38 μm.

[0209] Then, if Fig.16 As shown in (b), the elliptical shape of the green micro-LED (G-MLD) is designed to be 45μm×31μm. The long axis is 7μm larger than the diameter of the circular red micro-LED of 38μm, and the short axis is 7μm smaller than the diameter of the circular red micro-LED of 38μm. The long axis of 45μm is determined based on the engineering tolerances of the lithography and etching steps used to manufacture the micro-LEDs and assembly holes.

[0210] The diameter of the assembly hole of the circular red micro-LED is 42μm, and the engineering tolerance is about 3μm. As a result, the long axis of the green micro-LED is selected to be 45μm so that the green micro-LED will not be captured in the circular assembly hole of the red micro-LED.

[0211] Then, the oval shape of the blue micro-LED (B-MLD) is designed in the same way as the green micro-LED. The long axis is 7μm larger than the long axis 45μm of the green micro-LED (B-MLD), and the short axis is 7μm smaller than the short axis 31μm of the green micro-LED (B-MLD). As a result, Fig.16 As shown in (c), the elliptical shape of the blue micro-LED is designed to be 52μm×24μm.

[0212] Then, Fig.17 and Fig.18 This is data related to the DEP force simulated by COMSOL.

[0213] For example, Fig.17 This is the data on the change of DEP force with frequency when using a fixed voltage value (12Vpp).

[0214] Fig.18 The data is about the variation of DEP force with frequency when a fixed value of voltage (12Vpp) is applied using a modified RGB micro LED having a bottom metal layer on the lower end surface.

[0215] Specifically, Fig.17 The variation of DEP force of RGB micro-LED with frequency is shown. The applied voltage is fixed at 12Vpp and the interval between two assembly electrodes is fixed at 7.5μm. It is known that this condition is the optimal condition for use in display panel manufacturing.

[0216] In addition, the three LEDs were subjected to the maximum DEP force at about 100 kHz.

[0217] However, while the DEP force of GaN-based LEDs decreases above 100kHz, the DEP force of AlGaInP-based LEDs remains constant. Under this condition, the three types of LEDs cannot be assembled simultaneously with high yield due to the different frequency responses of the DEP force.

[0218] Since the DEP force is applied to polarized particles in a non-uniform electric field, it is affected by the electric field size, the frequency of the input voltage, the permittivity and conductivity of the particles (i.e., micro-LEDs), and the particle size (i.e., micro-LED chip size).

[0219] (The effect of LED chip size and electric field size on DEP force will be explained in detail in Method Experimental Example 2)

[0220] The difference in frequency response is attributed to the difference in conductivity between the AlGaInP-based layer 4 and the GaN-based layer 3 of the LED, as shown in Table 2. This can be explained by the inclusion of a dielectric (ε0ε r ) and the CM factor as a function of frequency for the conductivity contribution (σ).

[0221] At high frequencies, particle permittivity is the dominant factor, while at low frequencies in the range used in this embodiment, particle conductivity dominates. Therefore, the difference in DEP forces between GaN-based LEDs and AlGaInP-based LEDs can be explained by the difference in conductivity.

[0222] Then, as shown in Table 3 below, in order to overcome the difference in conductivity, a titanium bottom metal layer is added to the bottom surface of the LED to provide conductivity. Fig.18 The resulting DEP force response to frequency is shown.

[0223]

Table 3

[0224]

[0225] exist Figure 3 (a) and Figure 3 The structures of the micro-LEDs for the modified GaN-based and AlGaInP-based micro-LEDs are illustrated in (b).

[0226] Reference Fig.18 , the DEP force is improved for all LEDs, especially at high frequencies above 100kHz, and the GaN-based blue and green LEDs do not show a decrease in DEP force.

[0227] Therefore, the synchronous assembly frequency of RGB LEDs can be optimized in a wide frequency range according to the composition and design of the assembly substrate. If a bottom metal layer is added, the conductivity difference between the top and bottom surfaces of the micro-LED is maximized, so that the ratio of the DEP force applied to the bottom surface to the DEP force applied to the top surface can be increased by about 1.5 times.

[0228] As a result, the micro-LED structure with the additional bottom metal layer has a special technical effect, namely improving the function of the MDSAT to select the correct LED surface for assembly.

[0229] (Experimental Example 2)

[0230] Three factors that affect DEP force: LED chip size, electrode spacing, and dielectric layer of assembled electrodes

[0231] In the second experimental example, a COMSOL simulation was performed to study the influence of the mounting substrate and the LED chip size on the DEP force.

[0232] In particular, in this experimental example, the electrode gap (the distance between two mounting electrodes) and the dielectric layer of the mounting electrodes were studied as factors that affect the electric field size of the mounting substrate and the LED chip size.

[0233] For COMSOL simulation, a square wave AC voltage was used at the anode and the corresponding electrode was grounded on the assembly substrate as the input signal. The optimal conditions (12Vpp, 100kHz) were prepared for the peak-to-peak amplitude and frequency of the input AC voltage.

[0234] Fig.19 This is a schematic diagram of the 3D model used for COMSOL simulation.

[0235] Fig.19 The three factors that affect the DPE force are explained: the micro-LED chip, the electrode gap, and the dielectric layer on the assembled electrodes.

[0236] like Fig.19 As shown in (a), the LED chip of the embodiment may include a bottom metal layer such as titanium on the bottom surface, and may include a GaN-based micro-LED with a cylindrical shape.

[0237] The diameter of the micro-LED can range from 10 to 50 μm to evaluate the effect of LED chip size on the DEP force.

[0238] like Fig.19 As shown in (b) and (c), embodiments can use “gap ratio” instead of “electrode gap” to study the independent effects of two factors (electrode gap and LED chip size) on the DEP force.

[0239] The “gap ratio” can be defined as the ratio of the distance between two assembly electrodes to the size of the micro-LED chip, and the “electrode gap” is the distance between two assembly electrodes.

[0240] Fig.19 (b) shows the variation of DEP force with respect to LED size and gap ratio of SiO2 dielectric layer, Fig.19 (c) shows the variation of DEP force with respect to the Si3N4 dielectric layer for LED size and gap ratio.

[0241] Fig.19 (b) and Fig.19 (c) shows that the DEP force increases as the LED chip size increases and as the gap ratio of the SiO2 and Si3N4 dielectric layers decreases.

[0242] in addition, Fig.19 (b) and Fig.19 (c) shows that the dielectric layer on the assembly substrate (AS) is a necessary factor to affect the DEP force. Materials with higher dielectric constants (e.g. Si3N4 dielectric layer) will increase the DEP force under the action of Coulomb force, thus enabling the assembly of smaller LED chips.

[0243] The MDSAT method of the embodiment uses magnetic force to effectively transfer micro-LEDs, thereby innovatively improving the transfer yield, and can control the two forces (magnetic force and DEP force) so that they can compete with each other during assembly. Therefore, when the assembly process occurs near the assembly hole, the DEP force can be controlled to be greater than the magnetic force.

[0244] In the case of the MDSAT method, the magnetic force acting on the micro-LED varies with the distance between the micro-LED and the magnet, and can range from 1×10 -8 [N] to 1.2×10 -7 The range of [N].

[0245] Therefore, if micro-LEDs are to be successfully assembled, the DEP force can be controlled near the assembly hole to be greater than 1.2×10-7 [N].

[0246] Reference Fig.19 (b) For LED chip size, the research range is 10μm to 50μm. If a SiO2 dielectric layer is used, LED chips smaller than 20μm cannot be assembled, as a DEP force greater than 1.2×10-7[N] is required.

[0247] On the contrary, it has also been found that if a high permittivity material such as Si3N4 dielectric layer is used, it is also possible to assemble LED chips with a size of less than 20 μm required for low-cost industrial applications. Therefore, Si3N4 dielectric layer was selected in the experimental example.

[0248] Considering the process margins in the assembly electrodes on the assembly substrate and the power lines on the upper end of the LED chip, the size of the electrode gap and the size of the LED chip can be selected to be approximately 7.5 μm and approximately 38 μm, respectively, but are not limited thereto.

[0249] Next, the production of the assembly device of the embodiment will be described.

[0250] First, an assembly substrate may be fabricated.

[0251] For example, a three-layer of Mo / Al / Mo (20 / 100 / 20 nm) was deposited by electron beam evaporation and patterned to define the assembly electrode area. The patterning was performed by spin coating a photoresist (DNR L-300, DONGJIN SEMICHEM) at 2000 rpm for 40 seconds, soft baking at 100 °C for 2 minutes, and then using 110 mJ / cm 2 After UV exposure, the substrate was baked at 110°C for 2 minutes. Then, the Mo / Al / Mo layer was wet-etched with aluminum etching solution for 10 minutes, and then the substrate was rinsed with deionized water.

[0252] After this rinse, the Si3N4 dielectric layer of the assembly electrodes is deposited using plasma enhanced chemical vapor deposition (PECVD). The Si3N4 dielectric layer prevents corrosion of the assembly electrodes and also prevents electrochemical water splitting and short circuits caused by the metal layer at the bottom of the micro-LED forming a bridge between the anode and the common electrode.

[0253] Then, the assembly holes were made. The photoresist (WPR-1052, JSR) was spin-coated at 1500 rpm, soft-baked at 110°C for 2 minutes, and then heated at 200 mJ / cm2 After UV exposure, the substrate was baked at 110°C for 2 minutes. Finally, the substrate was developed using a developer (AZ-300MIF, MERCK) and baked in an oven at 200°C for 1 hour.

[0254] Then, the power cord can be made.

[0255] For example, after assembling the micro-LED on the assembly substrate, a photoresist (DPA-5000, DONGJIN SEMICHEM) layer was sprayed to fix the micro-LED, and then soft-baked at 100°C for two minutes, UV exposure without a photomask was performed, and then baked in an oven at 200°C for fifteen minutes.

[0256] Then, for planarization, a photoresist (SU-8, MICROCHEM) layer was spin-coated on the assembled substrate at a speed of 3000 rpm for 30 seconds. Then, the SU-8 was baked in an oven at 200° C. for one hour.

[0257] In order to set the electrical connection between the micro-LED and the power line, the n-type contact and p-type contact were defined on the micro-LED by spin coating a photoresist (GXR601, MERCK) on a photoresist (SU-8, MICROCHEM) and patterning it in a circular pattern.

[0258] Then, an ash process is performed using RIE (Reactive Ion Etching) to form circular contact holes in the SU-8, and the silicon dioxide passivation layer formed on the surface of the micro LED is etched through the holes using RIE.

[0259] After that, the photoresist (GXR601, MERCK) was removed. Then, circular contact holes of SU-8 were formed on the micro LED for n-type contact and p-type contact.

[0260] Then, the passivation layer (SiO2) of the micro-LED is etched within the contact holes.

[0261] Then, a transparent power line made of ITO (Indium Tin Oxide) was manufactured by a lift-off process. Fig.14 These transparent power lines are shown in b. An ITO layer is deposited on a patterned photoresist (DNR L-300, DONGJINSEMICHEM). Then, if DNR L-300 is removed using acetone, the ITO layer on the upper side is removed to generate transparent power lines.

[0262] Finally, Ti / Al power lines were also fabricated by lift-off process. The patterning of the power lines was achieved by depositing Ti / Al bilayer on the patterned DNRL-300 using electron beam.

[0263] Then, GaN-based micro-LEDs can be manufactured.

[0264] For example, a GaN-based epitaxial layer is prepared on a sapphire wafer, and ITO is deposited on it. To define the mesa, a photoresist (GXR601, MERCK) is spin-coated on the ITO at 2000 rpm for 30 seconds, soft-baked at 100°C for 2 minutes, then UV-exposed, developed with a developer (AZ-300MIF, MERCK) for 70 seconds, and finally hard-baked at 110°C for 2 minutes.

[0265] Then, a mesa shape is formed by etching the ITO / GaN-based epitaxial layer using an inductively coupled plasma (ICP) etching apparatus, and the remaining photoresist is removed.

[0266] Then, a photoresist (DNR L-300, DONGJIN SEMICHEM) was coated on top and patterned to define the outline of the micro-LED and pixelate it, and then the unmasked epitaxial area was ICP etched until the sapphire wafer was exposed.

[0267] Finally, n-type contact metal (Cr / Ti / Ni / Ti, 20 / 20 / 100 / 70nm) was fabricated on the n-region of the micro-LED by electron beam deposition and lift-off process.

[0268] Figure 3 (a) shows a schematic diagram of the n-type contact metal. The Ni layer built into the n-type contact metal can respond to magnetic force, thus playing a role in moving the micro-LED.

[0269] Then, if Figure 3 As shown in (a), PECVD is used to deposit a 500nm thick SiO2 (passivation layer) on the sidewalls and upper end surfaces of each micro-LED.

[0270] Under the action of the passivation layer, the leakage current caused by dry etching damage can be reduced. In addition, the passivation layer can improve hydrophilicity for free movement and prevent substrate adsorption (micro-LEDs attached to the surface of the assembly substrate) and micro-LED agglomeration. The passivation layer also has another advantage, that is, the micro-LEDs not assembled in the assembly holes are not adsorbed by the substrate and can be recycled. In addition, the passivation layer spatially separates the Ni layer from the surface of the micro-LED, thereby preventing the micro-LEDs from sticking to each other due to magnetization after magnetic manipulation.

[0271] Then, the fluid dispensing process of GaN-based micro-LEDs can be carried out.

[0272] After coating and patterning a photoresist (GXR601, MERCK) on the micro-LED, a PSA (pressure sensing adhesive) film was coated on it. Then, an LLO (laser-lift-off) process was performed to separate the sapphire wafer, and a Ti layer of about 100 nm was deposited on the exposed bottom surface of the micro-LED to improve the DEP force response (see Experimental Example 1). Finally, the micro-LED on the PSA film was immersed in acetone to dissolve the patterned photoresist, whereby the micro-LED was released from the PSA and dispersed in the acetone tank.

[0273] Then, AlGaInP-based micro-LEDs can be manufactured.

[0274] For example, an ITO layer is deposited on an AlGaInP based epitaxial layer grown on a GaAs wafer.

[0275] The subsequent processes are related to the manufacturing of the mesas and outlines of the micro-LEDs, which are similar to those of GaN-based micro-LEDs.

[0276] The same method was used in photolithography (spin coating, soft bake, UV exposure, development and hard bake). The same ICP etcher was used to etch the ITO / GaAs based epitaxial layer to form the mesa shape and remove the remaining photoresist.

[0277] Then, the micro-LED outlines were defined and pixelated by coating and patterning photoresist (DNR L-300, DONGJIN SEMICHEM) on top, and then the unmasked epitaxial areas were ICP etched until the GaAs wafer was exposed.

[0278] Finally, an n-type contact metal (AuGe / Au / Ti / Ni / Ti, 100 / 100 / 50 / 100 / 50 nm) was used by electron beam deposition, and then a 500 nm thick silicon dioxide layer was deposited on the sidewalls and upper end surface of the micro-LED.

[0279] Then, a fluid dispersing process of AlGaInP-based micro-LEDs may be performed.

[0280] For example, a photoresist (GXR601, MERCK) is coated on the micro LED, and then the side of the photoresist is attached to a glass wafer using a silicon adhesive.

[0281] Then, a CLO (Chemical Lift-Off) process is performed to remove the GaAs wafer using a solution (NH4OH:H2O2:H2O), and then RIE is used to remove the passivation layer (SiO2) formed between the micro LEDs.

[0282] Afterwards, a 100 nm Ti layer was deposited on the exposed bottom surface of the micro-LED to improve the DEP force response (see Experimental Example 1). Finally, the micro-LEDs on the glass wafer were immersed in acetone to dissolve the patterned photoresist on the top, so that the micro-LEDs were released from the glass wafer and dispersed in the acetone tank. Figure 3 (b) provides a schematic diagram of AlGaInP-based micro-LED.

[0283] Next, the MDSAT system of the embodiment will be described.

[0284] Assembly can be done with the assembly substrate facing downwards or with the micro-LEDs located on the bottom of the sink below the substrate. In this case, a stronger magnetic force is required to overcome gravity to pull the micro-LEDs up to the assembly substrate. The main advantage of this method is that unwanted particles that most likely do not have magnetic properties will not respond to the magnetic field and are excluded from the assembly process. On the other hand, since bending of the assembly substrate cannot be avoided, which may adversely affect assembly uniformity and yield, it has the disadvantage of needing to be minimized.

[0285] Next, the recycling of the micro LED of the embodiment will be described.

[0286] In the above-mentioned water tank chamber, in order to supply micro-LEDs, a glass tube array including a magnetic rod (called a magnetic tube) is prepared. The magnetic rod inside the magnetic tube moves vertically inward toward the end of the glass tube. As a result, the micro-LED is attached to or separated from the end face of the glass tube by the vertical movement of the magnet inside the glass tube. The weight of the amount supplied by each magnetic tube is 2 to 3 mg. According to the experimental example, when the weight of the LED is 2 to 3 mg, it will not affect the assembly yield. The magnetic tube array can make the LED fall directly above the assembly substrate of the water tank chamber. The magnetic tube array can be used again after the self-assembly process, and the LED is collected for recycling and prepared for the next execution.

[0287] On the contrary, since micro-LEDs are not attached to the surface of the assembly substrate, the MDSAT method does not form lumps (micro-LED aggregates) due to magnetization. Therefore, the MDSAT method has the advantage of being able to recycle micro-LEDs.

[0288] Industrial Applicability

[0289] The present invention can be used in the field of displays for displaying images or information.

[0290] The present invention can be used in the field of displays that use semiconductor light emitting devices to display images or information.

[0291] The present invention can be used in the field of displays that utilize micron-scale or nano-scale semiconductor light-emitting devices to display images or information.

Claims

1. A semiconductor light emitting device for a display pixel, wherein: include: A light emitting structure comprising a first conductive semiconductor layer, an active layer and a second conductive semiconductor layer; a first contact electrode, electrically connected to the first conductive type semiconductor layer; A metal layer, disposed under the first conductive type semiconductor layer; A second contact electrode is disposed on the second conductive type semiconductor layer; as well as A passivation layer, disposed on the light-emitting structure; The metal layer includes a magnetic substance, The weight ratio of the weight of the magnetic substance to the weight of the semiconductor light emitting device is 0.25% to 36.75%.

2. The semiconductor light emitting device for display pixel according to claim 1, characterized in that: The magnetic substance includes Ni.

3. The semiconductor light emitting device for display pixel according to claim 1, characterized in that: The thickness of the magnetic substance is 10 nm to 2300 nm.

4. The semiconductor light emitting device for display pixel according to claim 1, characterized in that: The first contact electrode is configured to surround the second contact electrode. The first contact electrode is electrically connected to the first conductive semiconductor layer whose upper side is partially removed from the light emitting structure.

5. A display device, characterized in that: include: a first assembled electrode and a second assembled electrode spaced apart from each other; a dielectric layer, disposed on the first assembly electrode and the second assembly electrode; an insulating layer having a predetermined assembly hole and disposed on the dielectric layer; as well as A semiconductor light emitting device, disposed in the assembly hole; The semiconductor light emitting device is the semiconductor light emitting device according to any one of claims 1 to 4.

6. The display device according to claim 5, wherein: The height of the assembly hole is 4.0 μm or more.

7. The display device according to claim 6, wherein: The height of the assembly hole is 4.5 μm to 5.0 μm.

8. The display device according to claim 5, wherein: The dielectric layer includes nitride.

9. The display device according to claim 8, wherein: The dielectric layer includes Si3N4.

10. The display device according to claim 5, wherein: A gap ratio, which is a ratio of a distance between the first assembly electrode and the second assembly electrode spaced apart from each other and a size of the semiconductor light emitting device, is 0.4 to 0.8.